Biocontrol of Aspergillus flavus on Peanut Kernels Using Streptomyces yanglinensis 3-10 - Shakeel, Qaiser; Lyu, Ang; Zhang, Jing; Wu, Mingde; Li, Guoqing; Hsiang, Tom; Yang, Long (Frontiers in Microbiology, 2018)
The bacterium, Streptomyces yanglinensis 3-10, shows promise in the control of many phytopathogenic fungi. In this study, S. yanglinensis and its antifungal substances, culture filtrate (CF3-10) and crude extracts (CE3-10), were evaluated for their activity in reducing growth and aflatoxin AFB1 production by Aspergillus flavus, both in vitro and in vivo on peanut kernels. The results showed that in dual culture conditions, S. yanglinensis reduced the mycelial growth of A. flavus about 41% as compared to control. The mycelial growth of A. flavus was completely inhibited on potato dextrose agar amended with CF3-10 at 3% (v/v) or CE3-10 at 2.5 μg/ml. In liquid culture experiments, growth inhibition ranged from 32.3 to 91.9% with reduction in AFB1 production ranging from 46.4 to 93.4% using different concentrations of CF3-10 or CE3-10. For in vivo assays, CF3-10 at 0.133 ml/g (v/w) or CE3-10 at 13.3 μg/g (w/w) reduced the postharvest decay of peanut kernels by inhibiting visible growth of A. flavus leading to an 89.4 or 88.1% reduction in AFB1 detected, respectively. Compared with the controls, CF3-10 and CE3-10 in A. flavus shake culture significantly reduced expression levels of two AFB1 biosynthesis genes, aflR and aflS. Furthermore, electron microscopy observation showed that CF3-10 (2%, v/v) caused hyphae growth to be abnormal and shriveled, cell organelles to degenerate and collapse, large vacuoles to appear. These results suggest that S. yanglinensis 3-10 has potential as an alternative to chemical fungicides in protecting peanut kernels and other agricultural commodities against postharvest decay from A. flavus.